Transport of Ultra-Large Cargo via Dynamic Janus Structure Reconstruction Enabled by Microrobots - Junmin Liu (5872562) (2025)
Electric field-driven micro/nanorobots (MNRs), combined with dielectrophoretic forces, provide a label-free approach for active cargo transport. However, their ability to transport cargo becomes severely limited when the cargo volume exceeds their own by several orders of magnitude. In this work, we propose a transport strategy that overcomes this limitation. Specifically, we introduce a “dynamic Janus structure reconstruction” transport strategy powered by asymmetric tubular electrically driven microrobots (ATEDMs). Under high-frequency electric fields, ATEDMs are attracted to the cargo, forming Janus-like structures and generating asymmetric electric field gradients around the contact surfaces, thus generating the dielectrophoretic forces required for cargo transport. The motion of the transported cargo is strongly influenced by the number and distribution of the ATEDMs, and the optimal range of ATEDM numbers for different motion patterns can be determined through probabilistic statistical methods. By integrating static magnetic fields, ATEDMs enable directed and controlled cargo transport. Additionally, we demonstrate the use of ATEDMs for palletizing cargo and transporting large biological tissues. This “dynamic Janus structure reconstruction” transport strategy allows for the transportation of cargoes more than 100,000 times larger than the volume of a single microrobot, providing an effective and versatile approach for transporting large-volume cargoes, thus expanding the application potential of MNRs in complex environments.